Organizational citizenship behavior of academic staff in Malaysian Research Universities - Hassan, Roshafiza; Asimiran, Soaib; Basri, Ramli; Omar, Zoharah (Human Resource Management Academic Research Society, 2021)
This study examined the level of organizational citizenship behavior of academic staff in Malaysian Research Universities. This study employed a quantitative descriptive survey whereby a total of 372 academic staff from five Research Universities were selected as samples for the study. An instrument consisting of 24 items was used to measure the level of academic staff’ organizational citizenship behavior at the workplace. The data were collected and analyzed using descriptive statistical tools (frequency, percentage, mean, and standard deviation). The descriptive analysis showed that the level of organizational citizenship behavior (mean = 5.91, SD = 0.56) was high. The result of this study also found that the highest dimension of organizational citizenship behavior was contributed by the dimension of courtesy (mean = 6.36, SD = 0.59), followed by the dimension of conscientiousness (mean = 5.96, SD = 0.74). The lowest dimension was contributed by Civic Virtue (mean = 5.55, SD = 0.80). Overall, academic staff’ organizational citizenship behavior was confirmed as a significant factor in enhancing institutional development in Malaysian Research Universities. Keywords: Organizational Citizenship Behavior, Academic Staff, Malaysian Research Universities, Higher Education.